Effectiveness Of Milkfish On Increasing Hemoglobin Levels In Pregnant Women At The Sebengkok Tarakan Health Center - Sarita,; Retno Palupi Yonni Siwi,; Erma Retnaningtyas,; Anggrawati Wulandari,; Asruria Sani, (Journal of Health Science Community, 2025)
The low behavior of checking hemoglobin levels in pregnant women is influenced by several factors, including the lack of knowledge of pregnant women regarding the importance of examinations and their lack of desire or willingness to know the benefits of checking hemoglobin levels. The aim of this research was to determine the effectiveness of milkfish in increasing hemoglobin levels in pregnant women. Method: The research design is pre-experimental with a one-group pre-post test design approach. The population is all 30 pregnant women who will have their hemoglobin levels checked at the Sebengkok Tarakan Community Health Center. The sampling technique used was total sampling and 30 respondents were found using the Wilcoxon statistical test. The results of the analysis of 30 respondents before being given milkfish, 20 respondents (60%) of them had a low category and after being given education 25 respondents (83.4%) of them had low HB. Results: Statistical test results using the Wilcoxon test with a value of p=0.001 (a<0.05), so it can be concluded that H0 is rejected and H1 is accepted, which means that there is an effect of the effectiveness of milkfish on increasing hemoglobin levels in pregnant women at the Sebengkok Tarakan Health Center Conclusion: Based on the research results, the category of checking hemoglobin levels in pregnant women. It is hoped that health workers will further improve their skills in communicating effectively with pregnant women so that they are willing to carry out examinations as a form of initial prevention in dealing with hemoglobin levels and feeling safe during the pregnancy process.